Partisipatif Konsep Rancangan Musala Baiturrohmah Gang Haji Nawi Jatimakmur Pondok Gede Kota Bekasi - Ali, Abdullah; Iswidodo, Iswidodo; Andayani, Keti; Susanto, Devit Budi; Koto, Despin Hidayat (LPPM Universitas Bung Karno, 2024)
Musala Baiturrohmah, located in Gang Haji Nawi, Jatimakmur Village, Pondok Gede District, Bekasi City, was initially a privately owned prayer facility. Over time, it has expanded to accommodate various community activities, serving not only as a place of worship but also for educational and social functions. Recognizing the need to enhance its facilities, the owner decided to renovate the Musala to include additional functional spaces and improve the surrounding environment. To achieve this, the owner collaborated with the Architecture Study Program at the Faculty of Engineering, Karno University. This partnership involved permanent lecturers, students, and alumni in forming a Community Service Team. The team undertook stages of field exploration, surveying, studying, design transformation, and reporting. Two design alternatives were developed for the Musala building, offering options that cater to the needs of both the owner and the local community.